2017
DOI: 10.1080/09687599.2017.1361812
|View full text |Cite
|
Sign up to set email alerts
|

How do Spanish disability support offices contribute to inclusive education in the university?

Abstract: This article analyzes the functioning of disability support offices and their contribution to inclusive education in seven Spanish universities from the perspective of staff. Using a qualitative methodology, interviews with office staff were conducted, and data were analyzed through an inductive coding system. The results are organized around five themes: characteristics of disability support offices, staff training, functions performed by different services, barriers and opportunities identified by office sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
(49 reference statements)
0
10
0
6
Order By: Relevance
“…For these faculty members, attending to the affective and emotional component of the student was an essential element for the development of inclusive practices in the classroom [20]. According to students with disabilities, these are the traits and characteristics that the ideal educator should have [52]. In fact, several studies have valued, in a very positive manner, the human and personal characteristics of the faculty members, demonstrating their positive association with the academic success of the students [25].…”
Section: Discussionmentioning
confidence: 99%
“…For these faculty members, attending to the affective and emotional component of the student was an essential element for the development of inclusive practices in the classroom [20]. According to students with disabilities, these are the traits and characteristics that the ideal educator should have [52]. In fact, several studies have valued, in a very positive manner, the human and personal characteristics of the faculty members, demonstrating their positive association with the academic success of the students [25].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning this question, participants were united in holding the view that inclusive education should embrace differences in the same school environment. Meanwhile, Tinklin, Riddell and Wilson (2004), Moriña, López-Gavirab and Morgadoc (2017) mentioned in their research that they found inclusive education necessary, while highlighting the limited range of physical opportunities, both at universities and in other educational institutions, as well as problems arising from the curriculum and the lack of equipped personnel. Ainscow andCésar (2006), Kozleski, Artiles, Fletcher andEngelbrecht (2009), Messiou (2017) emphasized that inclusive education is necessary and, in particular, that countries should develop policies for improving inclusive education.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The world practice shows that such socio-cultural factors as peer relationships and academic advisory contacts are more significant for the disabled than the classroom size, lighting, or handouts color [6]. However, this brings another problem: the lack of properly trained personnel who can facilitate the acquisition of higher education by people with disabilities via becoming their mentors and making the learning environment more accessible [7].…”
Section: People With Disabilitiesmentioning
confidence: 99%